The Survey of the Relationship Between Emotional Intelligence , Self-Efficiency & Job satisfaction among nurses - darvish, hassan; shabani, fatemeh; Ghasempuor, robab (Advances in Nursing & Midwifery, 2012)
Abstract: Background and aim: The most important goal of any organization is achieving the highest level or optimum productivity. An expert and efficient human resource is one of the most important tools for achieving the goals of the organization . Human resource plays an important role in increase or decrease of an organization’s productivity. The purpose of this study was to assess the relationship between emotional intelligence and self-efficacy and job satisfaction among nurses serving in teaching hospitals in Tabriz ,Iran. Materials and methods: A correlational design was used. The sample of the study includes 100 nurses ,which were randomly selected from 10 teaching hospitals in Tabriz ,Iran. Data were collection by Austin emotional intelligence questionnaire , job satisfaction , and Sharer self-efficiency Questionnaires.Validity of questionnaires were assured by content validity method. Data were analyzed by SPSS software ,correlation coefficient and multiple regression were used for computing the correlations among variables. Findings :, The relationship between emotional Intelligence and job satisfaction scores was 0.36 and this relationship was statistically significant (P: 0.01) .The relationship between emotional Intelligence and self-efficiency with correlation coefficient of 0.30 was also significant(P: 0.01). Conclusion : The result of the study indicated a significant relationship between emotional intelligence and self-efficiency, emotional intelligence and job satisfaction and self-efficiency among the nurses of educational and medical center in Tabriz Province in Iran and also the elements of emotional intelligence can anticipate job satisfaction and self-efficiency. Key words : Emotional intelligence , job satisfaction , self-efficiency , educational and medical centers in Tabriz Province .